Establishing the Effects of Internet Users on Inclusive Growth for the SADC Members States: Panel ARDL Approach - Ratombo, Ndivhuho Eunice; Mongale, Itumeleng Pleasure (International Journal of Economics and Financial Issues, 2024)
Inclusive growth initiatives had an influence on regional and global economies. Even though the association between information and communication technology (ICT) and economic growth has been investigated, a literature search shows that there is diminutive attention in establishing the effects of internet users on inclusive growth. This study intended to establish the effects of internet users on inclusive growth focusing on the selected SADC countries. The panel autoregressive distributed lag (ARDL) approach was employed from 2000 to 2020. The study discovered that internet users’ coefficient is positive and statistically insignificant in both the short-run and long-run period by repeating the same coefficient of (0.00). The findings of this study contribute to the understanding that internet usage is not a natural supporter of inclusive growth in the selected SADC countries. The study discovered that there is dearth of studies on inclusive growth studies. The novelty of this study is to establish the effects of internet users on inclusive growth. This study aspires to urged policymaker’s perceptions to increases the understanding and resonance of internet usage to respond to inclusive growth channels. Although there is a positive link but the benefits to promote inclusive growth are misdirected because of insignificant status.